Ethnomedicinal plants of Kathua district, J&K, India. (2nd August 2015) - Rao, P.K.; Hasan, S.S.; Bhellum, B.L.; Manhas, R.K.
Abstract: Ethnopharmacological relevance: Natural products, especially those derived from plants, continue to provide new and important leads in the drug discovery process. The first step in drug discovery is to document material traditionally used to treat an ailment. Documentation of such knowledge will lead to its conservation and facilitate future research on medicinal plant safety and efficacy to validate traditional use. The present study was undertaken with an aim to document the ethnomedicinal plants of Kathua district. Material and methods: The data were quantitatively analysed using indices like use-value (UV), informant consensus factor (ICF) and fidelity level (Fl). Results: A total of 112 informants (78 males and 34 females) were interviewed. They were using a total of 197 plants from 87 families and 174 genera for the ethnomedicinal purposes. The most dominant families were Fabaceae, Asteraceae and Lamiaceae. The most important plants of the study site on the basis of use-value were Mentha longifolia, Curcuma domestica, Zingiber officinale, Ocimum tenuiflorum, Adiantum capillus-veneris, Viola odorata, Mentha arvensis and Acorus calamus . The diabetes treatment had the maximum consensus (0.96 ICF) among the informants. Other important categories with high ICF values were gastrointestinal disorders and respiratory disorders. Total 23 species recorded 100% Fl. Medicinal plants with high Fl were Brassica rapa, Plumbago zeylanica, Punica granatum, Catharanthus rosea, Tinospora cordifolia, Acacia catechu, Aegle marmelos, Abrus precatorius, Oxalis corniculata, Nicotiana plumbaginifolia, Achillea millefolium, Tamarindus indica, Taxus baccata and Butea monosperma . Conclusion: The plants with high UV and Fl like M. longifolia, C. domestica, Z. officinale, O. tenuiflorum, A. capillus-veneris, A. calamus, B. rapa, P. zeylanica, C. rosea, T. cordifolia, A. catechu, O. corniculata, N. plumbaginifolia, A. millefolium, T. indica, T. baccata and B. monosperma should be analysed for pharmacological components and discovery of new drugs. Graphical abstract: